Fairness Perceptions and Job Satisfaction as Mediators of the Relationship between Leadership Style and Organizational Commitment - Zoran Sušanj; Ana Jakopec (Psychological Topics, 2012)
This study was conducted to explore the relationship between different leadership styles and organizational commitment. Furthermore, it attempts to clarify the role of justice perceptions and job satisfaction as mediators of the relationship between (active and passive/avoiding) leadership styles and organizational commitment. The structural equations modeling was used to analyze data collected from a sample of participants recruited from different organizations. The results have indicated that perceived supervisors active leadership styles are positively linked, and have both, direct and indirect effects on employees' organizational commitment. Perceived passive/avoiding leadership styles do not have any effect on organizational justice, job satisfaction and organizational commitment. Employees' job satisfaction depends directly on the level of organizational justice being perceived by the employees. Job satisfaction also significantly contributes to organizational commitment. Implications of the results concerning job and organizational attitudes are discussed, and suggestions for managing human resources are given.